Microbial Sensitivity to Antibacterial Drugs Used in the Treatment of Neodontogenic Abscesses and Phlegmons of the Maxillofacial Region in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Treatment and prevention of inflammatory diseases of the maxillofacial region in children represent one of the main problems of paediatric dentistry. According to the data of numerous authors purulent-inflammatory diseases of maxillofacial region make up to 21% of all surgical and 52% of dental diseases of childhood.